2014
DOI: 10.1186/2048-7010-3-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of varietal attributes on adoption of improved seed varieties: the case of sorghum in Kenya

Abstract: This paper examined the effect of variety attributes on adoption of improved sorghum varieties in Kenya. Using data from a random sample of 140 farmers, a multivariate probit was used to identify variety-specific drivers of adoption. The results on the perception of farmers variety attributes showed that improved varieties had desirable production and marketing attributes while the local varieties were perceived to have the best consumption attributes. Evidence further indicated that the major sorghum variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 6 publications
7
35
1
2
Order By: Relevance
“…A Wald test of joint significance of all the attribute variables yielded a Chi square statistic of 7.52 and p-value of 0.057 indicating that there is strong statistical evidence that varietal attributes jointly influence the decision to conserve quality planting materials for future planting. This finding is in line with past studies (Otieno et al, 2010;Timu, et al, 2012) that have showed that varietal attributes affect adoption of agricultural technologies or practices.…”
Section: Future Plantingsupporting
confidence: 94%
“…A Wald test of joint significance of all the attribute variables yielded a Chi square statistic of 7.52 and p-value of 0.057 indicating that there is strong statistical evidence that varietal attributes jointly influence the decision to conserve quality planting materials for future planting. This finding is in line with past studies (Otieno et al, 2010;Timu, et al, 2012) that have showed that varietal attributes affect adoption of agricultural technologies or practices.…”
Section: Future Plantingsupporting
confidence: 94%
“…Adoption literature typically argues that farmers' decision to adopt a new or improved technology is motivated by the incentives and capacity to do so (Otieno et al 2012;Timu et al 2014). The former usually focuses on the benefits of adopting improved technology, with benefits defined in terms of financial gain.…”
mentioning
confidence: 99%
“…Sorghum (Sorghum bicolor (L.) Moench) is one of the important staple crops for the world's poorest and food insecure people in the semi-arid regions of the world (Timu et al, 2012;Rohrbach et al, 2002;Doggett, 1988). In Kenya, sorghum is an important food crop and dietary staple in the country's arid and semi-arid lands which account for over 80% of the total land area.…”
Section: Introductionmentioning
confidence: 99%